Η6‐Arene‐Zirconium‐PNP‐Pincer Complexes: Mechanism of Their Hydrogenolytic Formation and Their Reactivity as Zirconium(II) Synthons. Issue 27 (3rd June 2016) - Plundrich, Gudrun T.; Wadepohl, Hubert; Clot, Eric; Gade, Lutz H.
Abstract: The cyclometalated monobenzyl complexes [(Cbzdiphos R ‐CH)ZrBnX]1   i Pr Cl and1   Ph I reacted with dihydrogen (10 bar) to yield the η 6 ‐toluene complexes [(Cbzdiphos R )Zr(η 6 ‐tol)X]2   i Pr Cl and2   Ph I (cbzdiphos=1, 8‐bis(phosphino)‐3, 6‐di‐ tert ‐butyl‐9 H ‐carbazole). The arene complexes were also found to be directly accessible from the triiodide [(Cbzdiphos Ph )ZrI3 ] through an in situ reaction with a dibenzylmagnesium reagent and subsequent hydrogenolysis, as exemplified for the η 6 ‐mesitylene complex [(Cbzdiphos Ph )Zr(η 6 ‐mes)I] (3   Ph I ). The tolyl‐ring in2   i Pr Cl adopts a puckered arrangement (fold angle 23.3°) indicating significant arene‐1, 4‐diido character. Deuterium labeling experiments were consistent with an intramolecular reaction sequence after the initial hydrogenolysis of a Zr−C bond by a σ‐bond metathesis. A DFT study of the reaction sequence indicates that hydrogenolysis by σ‐bond metathesis first occurs at the cyclometalated ancillary ligand giving a hydrido‐benzyl intermediate, which subsequently reductively eliminates toluene that then coordinates to the Zr atom as the reduced arene ligand. Complex2   Ph I was reacted with 2, 6‐diisopropylphenyl isocyanide giving the deep blue, diamagnetic Zr II ‐diisocyanide complex [(Cbzdiphos Ph )Zr(CNDipp)2 I] (4   Ph I ). DFT modeling of4   Ph I demonstrated that the HOMO of the complex is primarily located as a "lone pair on zirconium", with some degree of back‐bonding into the C≡N π* bond, and the complex is thus most appropriately described as a zirconium(II) species. Reaction of2   Ph I with trimethylsilylazide (N3 TMS) and2   i Pr Cl with 1‐azidoadamantane (N3 Ad) resulted in the formation of the imido complexes [(Cbzdiphos R )Zr=NR′(X)]5   i Pr Cl‐NAd and5   Ph I‐NTMS, respectively. Reaction of2   i Pr Cl with azobenzene led to N−N bond scission giving6   i Pr Cl, in which one of the NPh‐fragments is coupled with the carbazole nitrogen to form a central η 2 ‐bonded hydrazide(−1), whereas the other NPh‐fragment binds to zirconium acting as an imido‐ligand. Finally, addition of pyridine to2   i Pr Cl yielded the dark purple complex [(Cbzdiphos i Pr )Zr(bpy)Cl] (7   i Pr Cl ) through a combination of CH‐activation and C−C‐coupling. The structural data and UV/Vis spectroscopic properties of7   i Pr Cl indicate that the bpy (bipyridine) may be regarded as a (dianionic) diamido‐type ligand. Abstract : Cyclometalated monobenzyl complexes reacted with dihydrogen to yield η 6 ‐toluene complexes. The facile access to Zr II species without using highly reducing media but through hydrogenolytic cleavage of C−Zr bonds attests to the ability of the PNP‐pincers employed in this work to stabilize oxidation states other than +IV.